Low power 11T adder comparator design - C.M.R. Prabhu; Tan Wee Xin Wilson; T. Bhuvaneswari (Institute of Advanced Engineering and Science, 2020)
Comparator is a basic arithmetic component in a digital system and adders are the basic block of processor unit, the performance of adder will improve the system performance. The proposed 11T adder comparator is consists of three main components, namely XOR, inverter, and MUX logic. The circuit is designed and implemented based on top-down approach with 11 transistors. The proposed cell can be used at higher temperature with minimal power loss. It also gives faster response for the carry output. The proposed comparator circuit shows 63.80% improvement in power consumption than other circuits.